Preparing Nursing Students for Inter-Professional Collaborative Practice through Simulation-Based Inter-Professional Education: A Systematic Review - Utami Rachmawati; Muhammad Jauhar; Lita Heni Kusumawardani; Rasdiyanah Rasdiyanah; I Gusti Ayu Putu Desy Rohana (Poltekkes Kemenkes Semarang, 2022)
Background: Interprofessional Education (IPE) is an integrated education concept to improve collaboration capabilities initiated by WHO. Interprofessional collaboration practices are expected to minimize medication errors, improve quality of care and patient safety.Purpose: to analyze integrative research on the role of simulation-based interprofessional education (IPE) in preparing nursing students to an interprofessional collaboration practices. Methods: a systematic literature review search of four databases of indexed international journals, namely Science Direct, PubMed, ProQuest, and EBSCO was conducted. Inclusion criteria used for the search include original research, publication time 2016-2020, English-written, and accessible in full text. Studies were included if they have keywords of “knowledge” OR “perception” AND “interprofessional education” AND “nursing student”. Research articles were critically appraised and analyzed through a table containing the title, author, year, methodology, results, and recommendations. Lastly, data were synthesized narratively to address the study aims.Results: there were 13 research articles that met the criteria. IPE can be implemented in the form of simulations, elective courses, and workshops integrated with the curriculum. The results showed an improvement of knowledge, attitudes, perceptions, skills, readiness, and competency of nursing students after simulation-based IPE implementation. Finally, simulation-based IPE implementation prepares nursing students to excel in interprofessional collaboration practicesConclusion: simulation-based IPE should be integrated into the higher education health curriculum especially on clinical nursing practice and professional training. Further investigation is needed to identify relationship conflict, role conflict and performance satisfaction amongst IPC health staff.